Ayatollah Khomeini’s Thought on Islamic Government - Goudarzi, Masoumeh Rad (2009)
Ayatollah Khomeini Islamic government theory appeared in contrary with almost all governmental theories in the history of Shi‟a school of thought. His insist over necessity of establishment of Islamic government, the role he recognized for the jurists as administrators of Islamic country, the dimension of power he portrayed for the jurists, made his theory more unique and controversial. During a half of century from writing of his first political book in 1943 till his death in 1989 in the position of supreme leader of Islamic Republic of Iran, he gradually formed, developed, revised and formulated his Governance of the Jurist theory. Therefore, the first objective of the study is to understand the theoretical framework of Ayatollah Khomeini‟s governmental thought and how this framework affected his theorizing. The second objective aims to identifying the main structure of the theory and mutual interactions between different elements of it. To do this, research goes beyond available literature on Ayatollah Khomeini; to not only present his theory, but to reveal its underlying structure. The researcher by using Meta-theorizing as a means of attaining a deeper understanding of theory (Mu) and dealing with two dimensions of internal–social and internal- intellectual factors focused on revealing the role of social and historical events and elements as well as intellectual factors in formulating of his thought. The findings revealed that Ayatollah Khomeini approached the subject of Islamic government from an interdisciplinary approach: philosophical mystical, jurisprudential and political approaches. It was philosophy and mystic that convinced him manifestation of perfect human beings as caliphs of God in the earth is possible. Jurisprudence brought him to the conclusion that implementation of divine ordinance (Shari‟a) make ground to educate, reform and manifest of perfect human being, paving the way for temporal and spiritual salvation. By politics he believes that existence of none or anti Islamic government and unjust political order are the main impediments to implementation of Shari‟a and divine ordinance. All these convinced him that establishment of Islamic government under guidance of Guardian of Jurist is necessity. The research revealed that he by invoking to both transmitting and intellectual reasons tried to justify his belief about divine right of the jurist in administration of Islamic country and at the same time believed to dual structure of legitimacy (divine – popular) in defining the role of people in administration of the country. The internal-social factors as his background (family, religion and education) and his intellectual pursuits (activities and intellectual connections), leaved an undeniable effect on his thought and formulated the social and political structure of his thought. Moreover, the internal-intellectual factors as the dominant paradigms and schools both classic and contemporary in study of Islamic government affected and formulated the intellectual or the cognitive structure of his thought. In conclusion, Ayatollah Khomeini‟s Islamic government theory which formed, developed and formulated in the course of time, mainly is result of influential social, political and intellectual factors that he was affected by in his life time. Catching to underlying structures of theory as well as the foundations of thought, could be possible only by undertaking holistic and comprehensive study of both theory and theorist.